2010
DOI: 10.1080/00480169.2010.65061
|View full text |Cite
|
Sign up to set email alerts
|

Nodular gill disease causing proliferative branchitis and mortality in Chinook salmon (Oncorhynchus tshawytscha)

Abstract: Grossly, NGD can be mistaken for BGD; the distinction is important because chloramine-T, routinely used in the treatment of BGD, is ineffective for the treatment of NGD. Static formalin baths of 170 ppm (37% formaldehyde) for 1 hour, supplemented with oxygen, may reduce amoebic infections but should be used cautiously as treatment can precipitate mortality in fish with gill disease. Cues for the onset of NGD are not completely understood, although poor water quality and elevations in temperature are likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…The episodes of NGD described by Speare () in the Arctic char and by Tubbs et al () in the Chinook salmon showed that species of freshwater salmonids other than rainbow trout may be heavily affected by this disease. Tubbs et al () reported a daily mortality rate of 1.5% in Chinook salmon fry concomitant with non‐optimal water conditions because of the presence of suspended solids. Speare () described a case of NGD and BGD co‐infection in the Arctic char with high mortality rate.…”
Section: Environmental Parameters (Temperature Dissolved Oxygen and mentioning
confidence: 91%
See 2 more Smart Citations
“…The episodes of NGD described by Speare () in the Arctic char and by Tubbs et al () in the Chinook salmon showed that species of freshwater salmonids other than rainbow trout may be heavily affected by this disease. Tubbs et al () reported a daily mortality rate of 1.5% in Chinook salmon fry concomitant with non‐optimal water conditions because of the presence of suspended solids. Speare () described a case of NGD and BGD co‐infection in the Arctic char with high mortality rate.…”
Section: Environmental Parameters (Temperature Dissolved Oxygen and mentioning
confidence: 91%
“…In 1999, Speare described a mixed infection of bacterial gill disease (BGD), caused by Flavobacterium branchiophilum , and NGD in arctic char ( Salvelinus alpinus ) and rainbow trout farmed in eastern Canada. This was the first and only report of NGD in a salmonid species other than rainbow trout, until 2010, when Tubbs, Wybourne, and Lumsden () reported an episode of NGD in Chinook salmon ( Oncorhynchus tshawytscha ) farmed in freshwater raceways in New Zealand.…”
Section: Environmental Parameters (Temperature Dissolved Oxygen and mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, naked amoebae belonging to five genera, Acanthamoeba, Vermamoeba (formerly Hartmannella), Naegleria, Protacanthamoeba and Vannella, have been reported as potential agents characterized by morphological and molecular data (Dykov a et al 2010). As other studies of NGD in freshwater salmonids reported just a general amoebic aetiology (Speare 1999;Buchmann et al 2004;Antychowicz 2007;Tubbs, Wybourne & Lumsden 2010), a broader spectrum of agents is conceivable. To better understand the aetiology of NGD, data from outbreaks should more effectively characterize the amoebae by culture, morphology, and genetic studies.…”
Section: Introductionmentioning
confidence: 98%
“…As other studies of NGD in freshwater salmonids reported just a general amoebic aetiology (Speare ; Buchmann et al . ; Antychowicz ; Tubbs, Wybourne & Lumsden ), a broader spectrum of agents is conceivable. To better understand the aetiology of NGD, data from outbreaks should more effectively characterize the amoebae by culture, morphology, and genetic studies.…”
Section: Introductionmentioning
confidence: 99%